2021
DOI: 10.1007/s00330-021-08098-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver lymphatic anatomy and role in systemic lymphatic disease

Abstract: Objectives To characterize hepatic to systemic lymphatic connections in patients with systemic lymphatic disease using intra-hepatic lymphangiography and to compare outcomes after lymphatic intervention. Methods In this retrospective study, patients with intra-hepatic lymphangiography from May 2014 – April 2019 at our institution were included. Imaging review was performed and hepatic lymphatic connections and flow patterns were characterized. Clinical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This, in addition to high lymphatic afterload, reduces the lymphatic drainage capacity. However, not all patients with a Fontan circulation develop severe lymphatic abnormalities and it is hypothesized that the physiologic changes in venous and lymphatic congestion, plus an anatomical variant of the lymphatic vasculature, might lead to lymphatic failure in some of those patients [ 14 ]. This would explain why some patients with high CVP do not develop lymphatic failure and some who seem to have favorable hemodynamics might show severe lymphatic dysfunction [ 2 , 3 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, in addition to high lymphatic afterload, reduces the lymphatic drainage capacity. However, not all patients with a Fontan circulation develop severe lymphatic abnormalities and it is hypothesized that the physiologic changes in venous and lymphatic congestion, plus an anatomical variant of the lymphatic vasculature, might lead to lymphatic failure in some of those patients [ 14 ]. This would explain why some patients with high CVP do not develop lymphatic failure and some who seem to have favorable hemodynamics might show severe lymphatic dysfunction [ 2 , 3 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PB has also been observed in patients with variants of abnormal lymphatic anastomosis. 4 PB manifests clinically with the sudden onset of cough, wheezing, progressive dyspnea, refractory hypoxemia, chest or pleuritic pain, and occasionally fever. The most pertinent feature of PB is the formation of bronchial casts that can vary from rubbery structures filling the small airways to casts formed of amorphous material occupying the entire bronchial tree.…”
Section: Plastic Bronchitismentioning
confidence: 99%
“…5 In addition, PB sometimes presents without any known risk factors, in these cases, the casts are acellular which are often suggesting of an undetected underlying abnormality of the lymphatic drainage system. 4,6 Upon physical examination wheezing, attenuated breath sounds, and dullness to percussion can be observed. Radiological examinations such as chest X-rays and CT scans typically show partial atelectasis of the segments involved with compensatory hyperinflation of the unaffected segments.…”
Section: Plastic Bronchitismentioning
confidence: 99%
“…Biko et al recently published on the development of intrahepatic DCMRL (IH-DCMRL) (15). In a recent manuscript, Smith et al showed the correlation between the different hepatic lymphatic flow patterns and systemic lymphatic diseases (16). In addition, Lemley et al demonstrated that all patients with PLE have duodenal involvement with IH-DCMRL (17).…”
Section: Lymphatic Imagingmentioning
confidence: 99%
“…Irrespective of clinical presentation in patients with thoracic lymphatic flow disorders, if central lymphatic imaging demonstrates a normal thoracic duct flow pattern without perfusion of the mediastinum or the lungs, then TDE or TDL should not be performed as it can lead to worsening of symptoms. In these cases, the etiology is most often hepatopulmonary connections that bypass the central lymphatic conduction system, including the thoracic duct (Figure 7) (16). Selective embolization of hepatopulmonary connections will lead to a resolution of symptoms in most cases while maintaining central lymphatic flow.…”
Section: Plastic Bronchitismentioning
confidence: 99%